2022
DOI: 10.3390/foods11244079
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Far-Infrared Radiation Drying on Starch Digestibility and the Content of Bioactive Compounds in Differently Pigmented Rice Varieties

Abstract: Far infrared radiation (FIR) was applied to six rice varieties with different coloring of the pericarp (purple, red or non-pigment). Changes were determined in amylose content, in gelatinization parameters, in the content of bioactive compounds, in antioxidant activity and in the in vitro digestibility of pigmented rice as affected by FIR. The highest contents of amylose, total phenolic (TPC), total flavonoid (TFC) and total anthocyanins (TAC) were found in the purple and red varieties. Overall, FIR increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 45 publications
(104 reference statements)
0
1
0
Order By: Relevance
“…The cooking, color, texture gelatinization, microstructure, and pasting properties of stored brown rice were all improved by IR heating method with excellent drying as well as heating efficiencies (Ding et al, 2018). Ratseewo et al (2022) reported both positive as well negative impacts of far‐IR (FIR) treatment of normal rice and pigmented rice. Increase in total phenolic, anthocyanin, and flavonoid contents as well as antioxidant activity, were reported as positive impacts of FIR treatment.…”
Section: Introductionmentioning
confidence: 99%
“…The cooking, color, texture gelatinization, microstructure, and pasting properties of stored brown rice were all improved by IR heating method with excellent drying as well as heating efficiencies (Ding et al, 2018). Ratseewo et al (2022) reported both positive as well negative impacts of far‐IR (FIR) treatment of normal rice and pigmented rice. Increase in total phenolic, anthocyanin, and flavonoid contents as well as antioxidant activity, were reported as positive impacts of FIR treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is important to identify a suitable method to extend the shelf life, preserve the quality, and minimize nutrient loss during the preservation of shiitake mushrooms. Far infrared radiation drying utilizes the resonance between the radiation frequency and the inherent frequency of the moisture in materials to heat materials [11], and it has been widely used for drying biomaterials [12,13]. The far infrared radiation source releases energy that directly penetrates into the material, effectively heating both the surface and interior for ensuring consistent internal heating and swift dehydration.…”
Section: Introductionmentioning
confidence: 99%